Ancaman Pidana Mati Bagi Pelaku Tindak Pidana Begal Sebagai Solusi Mengurangi Tingkat Kejahatan Begal di Kota Makassar - Hamzah, Hamzah (Al-Daulah : Journal of Criminal Law and State Administration Law, 2016)
Criminal robber today increasingly made public Makassar City can not perform its activities properly, because it always felt threatened by street  actions  of  the  perpetrators.  From  the  research,  the  crime robber in Makassar more dominant influenced by the desire to emulate after watching a scene or event through electronic media TV has  indirectly  serving  news  or  violent  incidents  that  occurred  in various parts of the country water. The spectacle results become negative for the development of child education which is precisely through such education the children will try to do and practice sees. In sociology called "Society is imitation. Society is always in the process of imitating. When people are fed every day hardness values, rude, people eventually emulate. This statement is supported by data from several  actors  robber  who  were  interviewed  by  the  author.  In addition, the robber occurs due to the persuasion of his friends, The criminal robber never thought a result of this action will be able to bring the perpetrators to deal with the police and cause it to go into bars.